Sedimentation velocity analytical ultracentrifugation discrete species and size-distributions of macromolecules and particles - Schuck, Peter William 1968- (CRC Press, Taylor & Francis Group, 2016)
"The analysis of sedimentation velocity analytical ultracentrifugation has fundamentally changed in the last two decades, with the ability to solve the master equation of the sedimentation/diffusion process and the application of modern mathematical data analysis strategies substantially increasing hydrodynamic resolution of sedimenting particles. This book provides a systematic introduction to the theory of sedimentation velocity, and a comprehensive overview of experimental design strategies and data analysis. Areas of major focus are polydisperse macromolecules and nanoparticles, and the sedimentation of systems of reversibly interacting macromolecules, including protein interactions"...